Differential interleukin-6/Stat3 signaling as a function of cellular context mediates Ras-induced transformation - Leslie, Kenneth (BioMed Central, 2010)
INTRODUCTION: Tyrosine phosphorylated signal transducer and activator of transcription 3 (pStat3) is expressed in numerous cancers and is required for mediating tumorigenesis. Autocrine and paracrine interleukin (IL)-6 signaling is the principal mechanism by which Stat3 is persistently phosphorylated in epithelial tumors including breast, lung, colon and gastric cancer. The Ras oncogene mediates cellular transformation without evidence of pStat3 in cultured cells. However, non-tyrosine phosphorylated Stat3 was shown to function as a transcriptional activator, localize to the mitochondria and regulate ATP synthesis and mediate cell migration. Here we examined the role of Stat3 in Ras mediated transformation. METHODS: Ha-rasV12 transformed mammary epithelial cells (MCF10A-Ras) cells were transduced with a Stat3shRNA, IL-6shRNA and/or treated with inhibitors of Janus kinases (JAKs) to examine the role of the IL-6 signaling pathway in Ras mediated migration, invasion and tumorigenesis. RESULTS: Cellular migration, invasion, anchorage independent growth and tumorigenesis were largely abrogated in the Stat3-reduced cells compared to control cells. Analysis of MCF10A-Ras tumors revealed high levels of pStat3 and interleukin-6. Tumors derived from transgenic MMTV-K-Ras mice were also found to express pStat3 and IL-6. MCF10A-Ras cells, when grown in a three-dimensional Matrigel culture system revealed the appearance of the junctional protein E-Cadherin as a consequence of reducing Stat3 levels or inhibiting Stat3 activity. Decreasing IL-6 levels in the MCF10A-Ras cells abrogated tumorigenesis and reduced cell migration. By isolating Ras-expressing primary tumors and serially passaging these cells in two-dimensional culture led to a decrease in IL-6 and pStat3 levels with the reappearance of E-Cadherin. CONCLUSIONS: The cellular and environmental context can lead to differential IL-6/pStat3 signaling and a dependency on this cytokine and transcription factor for migration, invasion and tumorigenesis.